2021
DOI: 10.1007/s00259-021-05538-2
|View full text |Cite
|
Sign up to set email alerts
|

[68Ga]Ga-PSMA-11 PET imaging as a predictor for absorbed doses in organs at risk and small lesions in [177Lu]Lu-PSMA-617 treatment

Abstract: Introduction Patient eligibility for [177Lu]Lu-PSMA therapy remains a challenge, with only 40–60% response rate when patient selection is done based on the lesion uptake (SUV) on [68Ga]Ga-PSMA-PET/CT. Prediction of absorbed dose based on this pre-treatment scan could improve patient selection and help to individualize treatment by maximizing the absorbed dose to target lesions while adhering to the threshold doses for the organs at risk (kidneys, salivary glands, and liver). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…These results are in line with what we recently observed in a therapeutic 177 Lu-PSMA study on patients with low-volume metastatic hormone-sensitive prostate cancer (4,5). We saw that the dosimetry results based on posttherapeutic SPECT imaging in patients with a maximum of 10 prostate cancer metastases-or a very low volume of metastasis following the definition of Gafita et al-were comparable to previously reported results on patients with high-volume metastatic prostate cancer (6)(7)(8). This result suggests that the sink effect in the setting of lowvolume metastatic disease may be of less concern than is commonly anticipated.…”
supporting
confidence: 91%
“…These results are in line with what we recently observed in a therapeutic 177 Lu-PSMA study on patients with low-volume metastatic hormone-sensitive prostate cancer (4,5). We saw that the dosimetry results based on posttherapeutic SPECT imaging in patients with a maximum of 10 prostate cancer metastases-or a very low volume of metastasis following the definition of Gafita et al-were comparable to previously reported results on patients with high-volume metastatic prostate cancer (6)(7)(8). This result suggests that the sink effect in the setting of lowvolume metastatic disease may be of less concern than is commonly anticipated.…”
supporting
confidence: 91%
“…The use of [ 68 Ga]Ga-PSMA-11 PET/CT for an absorbed estimation of [ 177 Lu]Lu-PSMA RNT has not yet been evaluated extensively in literature. However, a recent study compared predicted absorbed doses to actual delivered doses; it did so through the use of [ 177 Lu]Lu-PSMA SPECT imaging data to determine population tissue effective half-times and estimate dosimetry using a single time point pretherapeutic [ 68 Ga]Ga-PSMA PET [102]. The PET/SPECT absorbed dose ratios were 1.01 ± 0.21 for the kidneys, 1.10 ± 0.15 for the liver, 1.20 ± 0.34 for the submandibular glands, and 1.11 ± 0.29 for the parotid glands.…”
Section: Predictive Dosimetrymentioning
confidence: 99%
“…Quantitation of tumour absorbed doses are very useful for dose-effect estimates and to avoid undertreating, but doses to organs at risk are important to ensure the safety of the radiopharmaceutical. Kidneys are considered one of the main organs at risk for many radionuclide therapies including 212 Pb-NG001 [25] and clinical studies with other PSMA-targeting radiopharmaceuticals have also shown salivary glands, liver, and bone marrow as normal tissues at risk [35][36][37]. Kidney dosimetry should be achievable with 212 Pb, but potential non-uniform uptake in the kidneys will be difficult to visualise and quantify.…”
Section: Discussionmentioning
confidence: 99%